Using Cellular Automata to Simulate Domain Evolution in Proteins - Xiao, Xuan; Xue, Guang-Fu; Stamatovic, Biljana; Qiu, Wang-Ren (Frontiers in Genetics, 2020)
Proteins play primary roles in important biological processes such as catalysis, physiological functions, and immune system functions. Thus, the research on how proteins evolved has been a nuclear question in the field of evolutionary biology. General models of protein evolution help to determine the baseline expectations for evolution of sequences, and these models have been extensively useful in sequence analysis as well as for the computer simulation of artificial sequence data sets. We have developed a new method of simulating multi-domain protein evolution, including fusions of domains, insertion, and deletion. It has been observed via the simulation test that the success rates achieved by the proposed predictor are remarkably high. For the convenience of the most experimental scientists, a user-friendly web server has been established at http://jci-bioinfo.cn/domainevo, by which users can easily get their desired results without having to go through the detailed mathematics. Through the simulation results of this website, users can predict the evolution trend of the protein domain architecture.